Clinicopathological characteristics of Xp11.2 translocation renal cell carcinoma in adolescents and adults: Diagnosis using immunostaining of transcription factor E3 and fluorescence in situ hybridization analysis. (13th November 2015) - Hirobe, Megumi; Masumori, Naoya; Tanaka, Toshiaki; Kitamura, Hiroshi; Tonooka, Akiko; Hasegawa, Tadashi; Tsukamoto, Taiji
Abstract : Objectives: To determine the rate and clinicopathological features of Xp11.2 translocation carcinoma using immunostaining of transcription factor E3 and fluorescence in situ hybridization analysis. Methods: We evaluated 638 patients with renal cell carcinoma treated at Sapporo Medical University Hospital, Sapporo, Japan, from 1990 to 2009 by reviewing all hematoxylin–eosin‐stained sections and carrying out immunostaining of transcription factor E3 for all cases. Fluorescence in situ hybridization analysis was carried out for patients with positive immunostaining or with findings suspicious for Xp11.2 translocation carcinoma on hematoxylin–eosin‐stained sections. In this analysis, we set a cut‐off level for split signals of at least 10% of nuclei. Results: Of the 631 patients, 20 (3.2%) were positive for immunostaining. Finally, five patients were diagnosed with Xp11.2 translocation carcinoma (0.8%). Four of these patients were female and aged less than 50 years, and three cases were diagnosed as stage IV with multiple regional lymph nodal or visceral metastases. The positive predictive value of immunostaining was 25%. Conclusion: Patients with Xp11 translocation renal cell carcinoma tend to be younger, more frequently female and diagnosed at a more advanced stage. Immunostaining followed by fluorescence in situ hybridization analysis is an accurate and cost‐effective approach for diagnosis of Xp11 translocation renal cell carcinoma.